2020
DOI: 10.1371/journal.pone.0239788
|View full text |Cite
|
Sign up to set email alerts
|

Soil mixing with organic matter amendment improves Albic soil physicochemical properties and crop yield in Heilongjiang province, China

Abstract: Crop productivity in Albic soil is poor, owing to poor soil physicochemical properties. Mixing of Aw layers, representing Albic soil, with B layers, could improve the physicochemical properties of Albic soil, which is characterized by poor humus on the topsoil and high penetration resistance. The objective of the present study conducted in 2015-2016 in an Albic soil region in Heilongjiang province, China, was to explore the effects of different soil mixing strategies on the physicochemical properties of Albic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Researchers Meng et al (2020) have attempted to improve Albic soils and increase crop yields primarily by increasing the amount of organic matter in the A-horizon and deeper over the past thirty years. The study showed that mixing horizon A, representing Albic soil, with horizon B improved the physicochemical properties of Albic soil, which has a low humus content in the upper soil horizon and high infiltration resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers Meng et al (2020) have attempted to improve Albic soils and increase crop yields primarily by increasing the amount of organic matter in the A-horizon and deeper over the past thirty years. The study showed that mixing horizon A, representing Albic soil, with horizon B improved the physicochemical properties of Albic soil, which has a low humus content in the upper soil horizon and high infiltration resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that pH strongly drives the community assembly, and that the keystone taxa appeared as Acidobacteria , Actinobacteria , and Nitrospira in the suspension of black soil. Meng et al [ 14 ] reported that an increase in soil organic matter can improve the soil physicochemical properties and crop yield in the black soil region of China. Therefore, we hypothesize that the organic fertilization could shift the keystone taxa, shift the microbial community assembly processes, and subsequently influence the crop yield in black soil regions.…”
Section: Introductionmentioning
confidence: 99%